Survey of educational impacts on herpetofauna in Nepal - Rai, Kalu Ram (Journal of Natural History Museum, 2008)
Conservation and development are co-conflicting terms of modern age. From the environmental point of view, the anthropogenic activities are often considered a leading factor for the depletion of wildlife. In the name of development and practical work in the educational institutes, the loss of a large number of frogs, lizards, and other dissecting animals, went either unnoticed or ignored. When India banned exporting the specimens into Nepal for biological utility, local collection increased and Nepal has felt an immediate need of conservation. Unavailability of specimen in so many Government and private educational institutes created an alarming situation. As concerns to the environmental aspects, there is an urgent need to control the injudiciously commercial collection of the specimens from their natural habitats. Keeping this view in mind, an attempt has been made in this paper to analyse the problems and to draw the attention of conservationists towards the wildlife farming, and breeding for scientific research, to fulfil the crucial necessities in the country. J. Nat. Hist. Mus. Vol.22, 2005 p.121-128